Aberrant expression of ecotropic viral integration site-1 in acute myeloid leukemia and acute lymphoblastic leukemia. Issue 2 (February 2015) - Su, Guangsong; Lian, Xueqi; Tan, Dongming; Tao, Huiquan; Liu, Hong; Chen, Suning; Yin, Hongchao; Wu, Depei; Yin, Bin
Abstract Ecotropic viral integration site-1 (EVI1) proto-oncogene expression in patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) requires further investigation. Here, EVI1 expression levels were measured in 216 Chinese patients with AML and 67 with ALL via quantitative real-time polymerase chain reaction. We found that EVI1 expressed at a high level (H-EVI1) was present in 11.1% of patients with AML versus 20.9% with ALL. Low levels of EVI1 expression occurred in 23.1% with AML versus 43.3% with ALL. This suggested that alteration of EVI1 expression was more profound in ALL than in AML. H-EVI1 was significantly enriched in 30–60-year-old patients. French–American–British (FAB) M3 subtype was significantly correlated with H-EVI1. Interestingly, we found that EVI1 expression was negatively associated with presence of the Philadelphia chromosome (Ph+) and MLL rearrangements in AML. However, Ph+, but not MLL rearrangements, was inversely correlated with EVI1 expression in B-ALL. These results for the first time suggest a mutually exclusive relationship between EVI1 expression and Ph+ karyotype.